A Job Task Analysis for Technicians in the Offshore Wind Industry. - Milligan, Gemma S.; O'Halloran, Joseph P.; Tipton, Michael J.; Blacker, Sam D.; Brown, Pieter E.H.; Siddall, Andrew G. (Work, 2019)
BACKGROUND: To establish whether an organization has a valid Physical Employment Standard (PES), it is important to determine those aspects of the job that are critical to operational success. OBJECTIVE: To determine the tasks of the Offshore Wind Industry (OWI) and whether the ability to undertake these tasks is adequately assessed. METHODS: The task analysis was completed through: observations; the research team undertaking tasks; reviewing operational manuals; and focus groups. In addition, a review of existing PES for the OWI was completed to determine whether standards matched with the results of the task analysis. RESULTS: Five critical tasks were identified: transfer from the vessel to the Transition Piece; ascent of the internal ladder; manoeuvre through hatches; torque and tensioning; and hauling a casualty up the tower. With the exception of aerobic capacity, the physical components required by Technicians are not assessed by the current medical standards, nor are these assessments standardized across companies. CONCLUSIONS: The Job Task Analysis undertaken can be used to inform decisions regarding the physical fitness requirements (selection), assessments and training of Technicians, with a view to ensuring that they are physically capable of undertaking the critical tasks without undue risk of injury to themselves or others.